Using Computerized Budget Simulation Models As a Teaching Device. - Sale, J. Timothy (The Accounting Review, 1972)
The article presents information on computerized budget simulation models, which can make an important contribution to accounting education. By simulating the budgetary process of the firm, they can provide a suitable method for studying the behavior of the budgeting system under a variety of conditions. They can provide insights into the interrelationships of the variables included in a budgeting system, and provide a valuable tool for experimentation with alternative sets of values for the decision variables included in the budgeting model. To allow accounting educators and students an opportunity to appreciate the potential of such computerized budget simulation models, Robert Seiler of the University of Houston has developed a computerized budget simulation model called FIMOF. The use of this computerized budget simulation model has illustrated to students the real meaning of comprehensive budgeting and the effectiveness of computer simulation as a tool for comprehensive profit planning.